KEUNGGULAN BERSAING DAN INOVASI PRODUK TERHADAP PENINGKATAN PENJUALAN SAN SAN BAKERY NGADILUWIH - Aprilia Dian Evasari; Bondan Subagyo; Desi Rahmawati (Universitas Tulungagung, 2023)
This study aims to see the effect of competitive advantage and product innovation on increased sales at San San Bakery Ngadiluwih. This research is a descriptive study with a quantitative approach. The sampling technique in this study used the Accidental sampling technique. The samples in this study were 99 respondents who purchased bread at San San Bakery Ngadiluwih. Data obtained through questionnaires or questionnaires, observation, and interviews. The method of analysis used in this study is multiple linear regression. From the results of the analysis that has been done, the results of the study show that competitive advantage has a partially significant effect on increased sales, product innovation has a partially significant effect on increased sales. Competitive advantage and product innovation simultaneously have a significant effect on increased sales.